Dyskinesias and associated psychiatric disorders following streptococcal infections. Issue 7 (21st June 2004) - Dale, R C; Heyman, I; Surtees, R A H; Church, A J; Giovannoni, G; Goodman, R; Neville, B G R
Abstract : Background: The classical extrapyramidal movement disorder following β haemolytic streptococcus (BHS) infection is Sydenham's chorea (SC). Recently, other post-streptococcal movement disorders have been described, including motor tics and dystonia. Associated emotional and behavioural alteration is characteristic. Aims: To describe experience of post-streptococcal dyskinesias and associated co-morbid psychiatric features presenting to a tertiary referral centre 1999–2002. Methods: In all patients, dyskinetic movement disorders followed BHS pharyngeal infection. BHS infection was defined by pharyngeal culture of the organism, or paired streptococcal serology. Movement disorders were classified according to international criteria, and validated by experienced child neurologists. Psychiatric complications were defined using ICD-10 criteria using a validated psychiatric interview. Results: In the 40 patients, the following dyskinetic movement disorders were present: chorea (n = 20), motor tics (n = 16), dystonia (n = 5), tremor (n = 3), stereotypies (n = 2), opsoclonus (n = 2), and myoclonus (n = 1). Sixty five per cent of the chorea patients were female, whereas 69% of the tic patients were male. ICD-10 psychiatric diagnoses were made in 62.5%. Using the same psychiatric instrument, only 8.9% of UK children would be expected to have an ICD-10 psychiatric diagnosis. Emotional disorders occurred in 47.5%, including obsessive-compulsive disorder (27.5%), generalised anxiety (25%), and depressive episode (17.5%). Additional psychiatric morbidity included conduct disorders (27.5%) and hyperkinetic disorders (15%). Psychiatric, movement, and post-streptococcal autoimmune disorders were commonly observed in family members. At a mean follow up of 2.7 years, 72.5% had continuing movement and psychiatric disorders. Conclusion: Post-streptococcal dyskinesias occur with significant and disabling psychiatric co-morbidity and are potential autoimmune models of common "idiopathic" movement and psychiatric disorders in children. Multiple factors may be involved in disease expression including genetic predisposition, developmental status, and the patient's sex.